Analysis of Salmonella typhi isolates from Southeast Asia by pulsed-field gel electrophoresis. - Thong, Kwai Lin; Puthucheary, S.; Yassin, R.M.; Sudarmono, P.; Padmidewi, M.; Soewandojo, E.; Handojo, I.; Sarasombath, S.; Pang, T. (American Society for Microbiology, 1995)
Pulsed-field gel electrophoresis (PFGE) revealed that multiple genetic variants of Salmonella typhi are simultaneously present in Southeast Asia and are associated with sporadic cases of typhoid fever and occasional outbreaks. Comparative analysis of PFGE patterns also suggested that considerable genetic diversity exists among S. typhi strains and that some PFGE patterns are shared between isolates obtained from Malaysia, Indonesia, and Thailand, implying movement of these strains within these regions of Southeast Asia, where they are endemic.